2023
DOI: 10.1021/jasms.3c00036
|View full text |Cite
|
Sign up to set email alerts
|

“Lab of the Future”─Today: Fully Automated System for High-Throughput Mass Spectrometry Analysis of Biotherapeutics

Hans E. Waldenmaier,
Elsa Gorre,
Michael L. Poltash
et al.

Abstract: Here we describe a state-of-the-art, integrated, multi-instrument automated system designed to execute methods involved in mass spectrometry characterization of biotherapeutics. The system includes liquid and microplate handling robotics and utilities, integrated LC-MS, along with data analysis software, to perform sample purification, preparation, and analysis as a seamless integrated unit. The automated process begins with tip-based purification of target proteins from expression cell-line supernatants, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Preparing large bsAb panels through combinatorial approaches such as cFAE typically requires the use of robotic liquid and microplate handling to ensure accuracy and minimize hands-on sample preparation time. Waldenmaier et al 150 have recently reported a fully automated mAb characterization workflow to support cell line selection, starting with mAb purification from cell-line supernatant, prior to intact, reduced, and peptide mapping LCMS analyses and data processing. The sample preparation stages of this procedure could potentially be modified to analyze panels of > 1000 bsAbs to support early screening campaigns, providing both time savings and improved data quality and consistency.…”
Section: Solutions To Enable Biophysical Validation Of Large Bispecif...mentioning
confidence: 99%
“…Preparing large bsAb panels through combinatorial approaches such as cFAE typically requires the use of robotic liquid and microplate handling to ensure accuracy and minimize hands-on sample preparation time. Waldenmaier et al 150 have recently reported a fully automated mAb characterization workflow to support cell line selection, starting with mAb purification from cell-line supernatant, prior to intact, reduced, and peptide mapping LCMS analyses and data processing. The sample preparation stages of this procedure could potentially be modified to analyze panels of > 1000 bsAbs to support early screening campaigns, providing both time savings and improved data quality and consistency.…”
Section: Solutions To Enable Biophysical Validation Of Large Bispecif...mentioning
confidence: 99%
“…These modifications can affect the charge of the protein, resulting in different forms of mAbs with varying charge properties. Therefore, it is essential to monitor charge heterogeneity during the production process to ensure that the final product is of the required quality. , …”
Section: Introductionmentioning
confidence: 99%